Forest growth trends in Canada - Craig Loehle; Kevin A. Solarik (The Forestry Chronicle)
Reports have identified changes in abiotic factors that potentially affect forest growth. A synthesis of studies of thesechanges in Canada over the past century was undertaken to evaluate how these factors may be influencing forest growth.Reviewed papers used multiple sources of data including long-term inventory plots, tree-ring reconstructions, historicalgeographic data, and forest growth models. The synthesis showed that several positive growth trends were found inBritish Columbia and eastern Canada, while results from the western interior of Canada were mixed. Trembling aspen(Populus tremuloides Michx.) dieback has been noted due to severe and prolonged drought events, with growth reduc-tions and mortality also documented for conifers in the western interior. Studies have also found slow forest expansionin many areas and at the northern tree-line. Overall, authors attributed positive forest growth trends to rising CO2 con-centrations, N deposition, increased precipitation, and increased temperature. Growth declines were generally attributedto a combination of increased temperatures and reduced precipitation. Studies also differed due to time periods consid-ered and how age effects were corrected. Methodological issues were identified that led to contradictory results betweensome studies. These issues need further study.